ERLINDUNGAN HUKUM TERHADAP ANAK KORBAN EKSPLOITASI SEKSUAL DITINJAU DARI ASPEK HUKUM PIDANA - Ermanita Permatasari (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2015)
Sexual exploitation of children is popularly called by CSEC or Sexual Exploitation of Children is a fundamental violation of the rights of the child. The infringement consisted of sexual abuse by adults, a third person, or others. The child is treated as a sexual object. Sexual exploitation of children is a form of coercion and violence against children, and lead to forms of forced labor and slavery. Sexual exploitation of children is now becoming a matter of extreme concern that has yet to be resolved. Sexual exploitation of children is a crime against humanity that must be prevented and eliminated, because in addition to violating the Convention on Rights of the Child (CRC), also contrary to religious and cultural norms. Criminal law protection of child victims of sexual exploitation embodied in Section 76 I and 88 Law of the Republic of Indonesia Number 35 of 2014 on the Amendment of Act No. 23 of 2002 on Child Protection. A form of legal protection for children as victims of CSEC in the jurisdiction of Police of East Lampung, among others Providing services optimally to the victim in the framework of the complaint and the disclosure of cases involving the victims, facilitate the implementation of a post mortem on the victim, Concealing the identity of the victim during the process of examination and Facilitating the process of assistance and rehabilitation to the victims.